Questioning the Dimensions of Digital Surveillance and Parental Supervision: YouTube Challenges and Video Recommendation System - Tuğça Poyraz; Elif Özuz Dağdelen (Journal of Economy Culture and Society, 2023)
The development of communication technologies and the active use of social media platforms have led to the fusion of the existing culture with the digital culture formed in this field. While digital culture enables individuals to transfer their norms and values to social media platforms, on the other hand, it has adapted its norms and values to daily culture. YouTube has become one of the main social media platforms on which this culture is especially based and where it is defined as participatory culture. It is thought that especially younger age groups are included in this culture and that provides an occasion for them to take part in surveillance practices by providing data to big data. In this study, to make sense of this situation, the theories of digital sociology and digital surveillance sociology were rethought and qualitative research was conducted to look at the ways in which children aged 9-13 are involved in big data. The study focuses on their YouTube practices, especially their experiences of the challenges connected with using YouTube and the video recommendation system, and suggests precautions where necessary. After conducting netnography on YouTube, the sample of the study was determined using purposeful sampling and snowball sampling techniques, and in-depth interviews were conducted with 23 children upon obtaining consent forms from their families. The findings of the research revealed that usage patterns of social media platforms and the resulting consequences can reach very dangerous levels and that the degree of parental supervision should be reconsidered.